Carbamoyl‐phosphate synthetase 2, aspartate transcarbamylase, and dihydroorotase (cad) regulates Notch signaling and vascular development in zebrafish. Issue 1 (17th November 2014) - Coxam, Baptiste; Neyt, Christine; Grassini, Daniela R.; Le Guen, Ludovic; Smith, Kelly A.; Schulte‐Merker, Stefan; Hogan, Benjamin M.
<x xml:space="preserve">Abstract</x> Background : The interplay between Notch and Vegf signaling regulates angiogenesis in the embryo. Notch signaling limits the responsiveness of endothelial cells to Vegf to control sprouting. Despite the importance of this regulatory relationship, much remains to be understood about extrinsic factors that modulate the pathway. Results: During a forward genetic screen for novel regulators of lymphangiogenesis, we isolated a mutant with reduced lymphatic vessel development. This mutant also exhibited hyperbranching arteries, reminiscent of Notch pathway mutants. Positional cloning identified a missense mutation in the carbamoyl‐phosphate synthetase 2, aspartate transcarbamylase, and dihydroorotase (cad) gene. Cad is essential for UDP biosynthesis, which is necessary for protein glycosylation and de novo biosynthesis of pyrimidine‐based nucleotides. Using a transgenic reporter of Notch activity, we demonstrate that Notch signaling is significantly reduced in cadhu10125 mutants. In this context, genetic epistasis showed that increased endothelial cell responsiveness to Vegfc/Vegfr3 signaling drives excessive artery branching. Conclusions: These findings suggest important posttranslational modifications requiring Cad as an unappreciated mechanism that regulates Notch/Vegf signaling during angiogenesis. Developmental Dynamics 244:1–9, 2015. © 2014 Wiley Periodicals, Inc.